Introduction of Performance Budgeting in National Highways Ministry of Transport - Planning Commission, Government of India (Planning Commission, Government of India, 1966)
This report presents a pilot study on performance budgeting for India's National Highways, initiated by the Ministry of Transport in February 1966. It introduces a budget model focused on tangible outcomes rather than mere expenditure categories, aiming to increase accountability and effectiveness in governmental spending. Key sections of the report outline the principles of performance budgeting, highlighting the necessity for a modern financial management framework that ties budget requests to specific program achievements. It discusses ongoing budgeting practices under current capital and revenue expenditures, and identifies clustered projects such as road construction and maintenance efforts. The report emphasizes the development of physical metrics for performance evaluation and the establishment of a system for regular progress reporting, essential for management oversight and legislative accountability.
Development Administration Unit Management & Administration Division Committee on Plan Projects Planning Commission
Committee on Plan Projects Planning Commission, Government of India
Keywords: Performance Budget Concept; Current Challenges; Proposed Improvements; Reporting Protocols; National Highways; Ministry of Transport